THE ROLE OF SCHOOL ENVIRONMENT IN CULTIVATING MORALS IN ELEMENTARY SCHOOL AGE CHILDREN AT SDN 15, LUBUKLINGGAU CITY - Pajaria (CV Grasta Glory, 2025)
The school environment is a unified space in a formal educational institution that systematically implements guidance programs to help students develop their potential optimally, covering moral, spiritual, intellectual, emotional, social, and physical-motor aspects. Schools are not merely places for the